DIMENSI CORPORATE ENTREPRENEURSHIP DAN PENGARUHNYA TERHADAP KINERJA PERUSAHAAN - Mulyanto, Kukuh (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2013)
This research examine the effects of corporate entrepeneurship on firm performance. Summary said that corporate entrepeneurship is positively effected to firm performance